تأثير تمارين الكروس فيت على الجانب البدني لدى لاعبي كرة القدم هواة صنف ناشئين - ذياب وليد (My University, 2024)
الملخص: هدفت دراستنا إلى التعرف على استخدام تدريبات CROSS FITوتأثيرها فيتحسين الجانب البدني لدى لاعبي كرة القدم أشبال,حيث استخدمنا المنهج التجريبيلملائمته طبيعة البحث, وتمثل مجتمع البحث في مجموعة لاعبين فيكرة القدم فئة ناشئين U17,حيث تكونت عينة دراستنا من 35 لاعبا ينتمون إلى نادينادي رياضي بولاية سوق أهراس وتم اختيار العينة بالطريقة القصدية, وقد استخدمنا مجموعة من الاختبارات البدنية والمتمثلة في اختبار سارجنت واختبار القفز الأفقي واختبار الجري المكوكي واختبار جري 1500 متر واختبار جري 200 متر, وقد اعتمدنا على برنامج الحزمة الاحصائية SPSS 25, وقد أسفرت نتائج الدراسة إلى:  تمارين الكروس فيت أدت إلى تطوير صفة التحمل لدى لاعبي الكرة القدم فئة أشبالمستوى قياس بعض المؤشرات البدنية لدى لاعبي كرة القدم يتراوح بين جيد وجيد جدا.  هناك فروق ذات دلالة إحصائية بين الاختبار القبلي والبعدي في صفة التحمل لدى لاعبيكرة القدم صنف أشبال تعزى لتمارين الكروس فيت.  هناك فروق ذات دلالة إحصائية بين الاختبار القبلي والبعدي في صفة القوة لدى لاعبي كرة القدم صنف أشبال تعزى لتمارين الكروس فيت. Abstract: Our study aimed to identify the use of CROSS fit training and its impact in improving the physical aspect of Cubs football players, where we used the experimental approach to suit the nature of the research, and the research community was represented in a group of football players, U17 junior category, where our study sample consisted of 35 players belonging to a sports club in the state of Souk ahras and the sample was selected by the intentional method, we used a set of physical tests , represented by the Sargent test, horizontal jump test, shuttle run test, 1500 meter run test, and running 200 meters, we have relied on the program of the statistical package SPSS 25, the results of the study have resulted in:  The level of measurement of some physical indicators in football players ranges from good to very good.  There are significant differences between the pre-and post-test in the endurance of football players Cubs Class attributed to CrossFit exercises.  There are statistically significant differences between the pre-and post-test in the strength trait of Cubs-class football players attributable to CrossFit exercises. Résumé: Notre étude visait à identifier l'utilisation de l'entraînement CROSS fit et son impact sur l'amélioration de l'aspect physique des joueurs de football Cubs, où nous avons utilisé l'approche expérimentale en fonction de la nature de la recherche, et la communauté des chercheurs était représentée dans un groupe de joueurs de football, catégorie junior U17, où notre échantillon d'étude était composé de 35 joueurs appartenant à un club sportif de l'État de Souk ahras et l'échantillon a été sélectionné par la méthode intentionnelle, nous avons utilisé un ensemble de tests physiques, représentés par le test de Sargent, le test de saut horizontal, le test de course en navette, le test de course de 1500 mètres et la course à pied 200 mètres, nous nous sommes appuyés sur le programme du progiciel statistique SPSS 25, les résultats de l'étude ont abouti à:  Le niveau de mesure de certains indicateurs physiques chez les joueurs de football varie de bon à très bon.  Il existe des différences significatives entre le pré et le post-test dans la classe d'endurance des oursons des joueurs de football attribués aux exercices CrossFit.  Il existe des différences statistiquement significatives entre le pré-et le post-test dans le trait de force des joueurs de football de classe Cubs attribuables aux exercices CrossFit.
دراسة ميدانية للاعبي كرة القدم ناشئين نادي افاق المراهنة
Keywords: الكروس فيت; الجانب البدني; كرة القدم; CrossFit; physical aspect; football: CrossFit; aspect physique